Effect of gestational diabetes mellitus on testis and pancreatic tissues of male offspring - Turk, G.; Risvanli, A.; Ceribasi, A. O.; Sonmez, M.; Yuce, A.; Guvenc, M.; Yaman, M. (Wiley, 2018)
The purpose of this study was to determine the effect of gestational diabetes mellitus (GDM) on some reproductive characteristics, testicular and pancreatic oxidative status and pancreatic endocrine receptor densities of male offspring at post-pubertal stage. A total of 36 1-day-old Wistar Albino male offspring including 12 pups of nontreated mothers (control group), 14 pups of 40mg/kg STZ-injected mothers (STZ-40 group) and 10 pups of 60mg/kg STZ-injected mothers (STZ-60 group) were used. The offspring were euthanised on post-natal day 60, their blood, reproductive organs and pancreatic tissues were obtained and examined. When compared with the control group, there was a significant decrease in body and absolute reproductive organ weights, serum testosterone level, testicular and pancreatic catalase activities, pancreatic glutathione level, epididymal sperm concentration of both STZ-40 and STZ-60 groups as well as in testicular glutathione level of only STZ-60 group. Significant increases were determined in testicular and pancreatic malondialdehyde level and glutathione peroxidase activity in both groups and in fasting serum glucose of only STZ-60 group in comparison with the control group. Although some histopathological damages were observed in testes of both STZ-40 and STZ-60 groups, there were no detectable differences between the groups in density of insulin, glucagon and somatostatin receptors in pancreas. In conclusion, GDM has negative effects on reproductive efficiency and testicular-pancreatic tissue oxidant/antioxidant balance of male offspring at post-pubertal stage.
Keywords: gestational diabetes mellitus; offspring; pancreas; sperm; testis